Clove Flower Extract (Syzygium aromaticum) Has Anticancer Potential Effect Analyzed by Molecular Docking and Brine Shrimp Lethality Test (BSLT) - Eduardus Bimo Aksono; Aprilia Cahya Latifah; Lucia Tri Suwanti; Kautsar Ul Haq; Herinda Pertiwi (Veterinary Medicine International)
Various anticancer medications have been discovered due to advances in the health care industry, but they have undesirable side effects. On the other hand, anticancer drugs derived from natural sources have low side effects, making them excellent for cancer therapy. This study aims to evaluate the effect of clove flower extract (Syzygium aromaticum) as a potential anticancer agent by determining grid-score values using molecular docking and LC50 values using the brine shrimp lethality test (BSLT) technique. As animal models, three hundred larvae of Artemia salina leach were divided into six groups. Each group has ten larvae that have undergone five replications. The clove flower extract concentration in the treatment media was 50 ppm (T1), 250 ppm (T2), 500 ppm (T3), 750 ppm (T4), 1000 ppm (T5), and 0 ppm (seawater) as the control. The probit analysis of Artemia Salina leach mortality percentage data. The results indicated that the clove flower extract (Syzygium aromaticum) is harmful to larvae with LC50 values of 227,1 g/ml or in the equation y = 2,8636 x – 1,7466 with an R2 value of 0.9062. According to molecular docking, eugenol acetate (grid-score −42.120834) has a close relationship with the cognate enzyme nitric oxide synthase (3E7G) based on its proximity to the grid score value (grid-score −61.271812). Therefore, clove flower extract has the potential to act as an anticancer medication. Based on the grid-score proximity, eugenol acetate is close to the homologous enzyme nitric oxide synthase (3E7G). Inhibition of nitric oxide synthase also shows a reduction in cancer cell proliferation.